Hubungan Faktor Risiko dan Fisioterapi terhadap Pemulihan Fungsional Pasien Post Stroke: Studi Potong Lintang di Praktek Fisioterapi Karya Suci - Yuli Ayunara Napitu; Sondang Sidabutar; Yunardi Yunardi (Lembaga Pengembangan Kinerja Dosen, 2025)
Functional recovery after stroke is a complex process and is influenced by various factors, both previous health conditions and the quality of rehabilitation interventions. This study aims to analyze the relationship between cardiometabolic risk factors (age, hypertension, diabetes mellitus, and comorbidities) and physiotherapy characteristics on the level of functional recovery of post-stroke patients at Karya Suci Physiotherapy Practice. The study used a cross-sectional design involving 40 post-stroke patients in 2025. Data analysis was performed using the chi-square test and Spearman correlation at a significance level of α = 0.05. The results showed that 20% of patients achieved functional independence. Hypertension (p = 0.003), diabetes mellitus (p = 0.008), and body mass index (p = 0.000) were significantly associated with the level of independence. Frequency (r = 0.820), duration (r = 0.442), and physiotherapy involvement (r = 0.776) had a positive correlation with functional improvement. Multimodal therapy combining Infrared, TENS, active exercise, and the Bobath method was shown to be more effective than therapy without electrotherapy (p = 0.002).